A Case of Lung Cancer Unexpectedly Detected with 99mTc (V)-DMSA Whole-Body/SPECT Imaging - Gharepapagh, Esmaeil; Namvar, Leila; Rezaei, Sahar (World Journal of Nuclear Medicine, 2025)
In terms of cancer-related deaths, lung cancer is the most common type. To prevent this malignant and dangerous disease from progressing, early and differential diagnoses are very critical. A combination of dimercaptosuccinic acid and pentavalent 99mTc under alkaline conditions, 99mTc (V)-DMSA, can be used for malignant tumors' early diagnosis and prognosis. The 99mTc (V)-DMSA radiotracer is most commonly used for follow-up of medullary thyroid cancer metastases, but it is also successful in lung cancer and other malignancies. In this case, a 65-year-old woman with a recent history of nonproductive cough and mild dyspnea and suspicious small masses of lungs in computed tomography was selected for imaging with 99mTc (V)-DMSA to evaluate the condition of radiotracer uptake in the lung masses. The whole-body and single-photon emission computed tomography imaging with semiquantitative analysis showed abnormal uptakes in the lesions and the patient underwent to transbronchial biopsy and bronchial washing cytology that confirmed non-small cell lung cancer.
Keywords: lung cancer; 99mTc (V)-DMSA; SPECT imaging